The History of Ukrainian-Jewish Relations Through the Prism of Fiction - Kovbasenko, Yurii; Levitas , Felix; Salata, Oksana (Studia Philologica, 2025)
Ukrainian war, we are witnessing the emergence of civil society in our country. Various national communities, whose representatives are citizens of our country, are participating in these political processes. In this context, the aim of the study is to examine and analyze the centuries-old history of Ukrainian-Jewish relations through the prism of works of fiction.